A Metallosupramolecular Coordination Polymer for the ‘Turn‐on’ Fluorescence Detection of Hydrogen Sulfide - Dr. Joydev Hatai (ChemistryOpen, 2020)
Abstract A coumarin based probe for the efficient detection of hydrogen sulfide in aqueous medium is reported. The investigated coumarine‐based derivative forms spherical nanoparticles in aqueous media. In presence of Pd2+, a metallosupramolecular coordination polymer is formed, which is accompanied by quenching of the coumarin emission at 390 nm. Its Pd2+ complex could be used as a probe for chemoselective detection of monohydrogensulfide (HS−). Presence of HS− leads to a'turn‐on' fluorescence signal, resulting from decomplexation of Pd2+ from the metallosupramolecular probe. The probe was successfully applied for qualitative and quantitative detection of HS− in different sources of water directly collected from sea, river, tap and laboratory drain water, as well as in growth media for aquatic species.